THE ISSUE OF TEACHERS’ PROFESSIONAL AND METHODICAL UNIT FORMATION AND DEVELOPMENT IN PEDAGOGY - MARDOYAN, RUZANNA; ARAQELYAN, MARINE (Main Issues Of Pedagogy And Psychology, 2015)
The current paper presents the issues related to the process of formation and development of the teachers’ professional and methodical units within various cycles of pedagogy. In addition, it highlights the significance of the role of teachers’ collaboration, cooperation, awareness of different types of integration within these units for the benefit of the quality of teaching /learning process. The paper states that multilayered analysis of teachers’ engagement into the educational environment will foster them to function as empowered and empowering specialists to establish new paths in teaching.